2019
DOI: 10.1111/jocs.14072
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of long‐term outcome after septal myectomy in symptomatic hypertrophic obstructive cardiomyopathy patients with previous alcohol septal ablation and residual obstruction

Abstract: Background and aim Recently alcohol septal ablation (ASA) has emerged as an alternative treatment for drug‐refractory hypertrophic obstructive cardiomyopathy (HOCM) and a subgroup of HOCM patients with previous ASA may need myectomy. However, subsequent outcome and mechanism of residual obstruction has not been determined. This study aims to determine outcome after myectomy and mechanism of residual obstruction in HOCM patients with previous ASA. Methods From February 2009 to June 2017, 38 HOCM patients with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…115 The vast majority of patients incur left bundle branch as a result of the operative resection which does not influence later clinical course. 112 Surgeons performing myectomy after an unsuccessful ASA report less consistent operative results and a higher rate of complete heart block, [116][117][118] underscoring that myectomy is the preferred initial procedure to avoid myocardial scarring, heart block and other potential adverse consequences of ASA.…”
Section: Clinical Results Of Surgical Myectomymentioning
confidence: 99%
“…115 The vast majority of patients incur left bundle branch as a result of the operative resection which does not influence later clinical course. 112 Surgeons performing myectomy after an unsuccessful ASA report less consistent operative results and a higher rate of complete heart block, [116][117][118] underscoring that myectomy is the preferred initial procedure to avoid myocardial scarring, heart block and other potential adverse consequences of ASA.…”
Section: Clinical Results Of Surgical Myectomymentioning
confidence: 99%
“…Nevertheless, LVEDD was not an independent predictor in the further analysis. Zhu et al [39] enrolled 38 HOCM patients with previous alcohol septal ablation who underwent surgical septal myectomy and found postoperative LVEDD (HR � 1.14; 95% CI � 1.05-1.23; P � 0.002) was an independent predictor of adverse events. Seiler et al [40] indicated that HCM patients with chamber dilatation had a worse prognosis than those without, particularly for the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In 1998, the first PTSMA was performed in China. PTSMA has gradually become an important method for the treatment of HOCM in China [13]. However, the injection of absolute ethanol in the wrong location during surgery may cause myocardial necrosis and scar formation, which may lead to severe complications, such as complete heart block, persistent ventricular tachycardia, ventricular fibrillation, cardiac arrest, ventricular septal perforation, and pericardial effusion [14].…”
Section: Asamentioning
confidence: 99%
“…The optimum dose of alcohol injected into the target blood vessel can produce the most appropriate infarct size, so as to achieve the greatest clinical and hemodynamic effects [12]. Zhu et al [13] pointed out that the main reason for residual obstruction after PTSMA may be that degree and location of myocardial infarction caused by PTSMA are not easily controllable. However, compared with long-term event-free survival after ventricular septal resection, PTSMA is generally preferred.…”
Section: Asamentioning
confidence: 99%